Legal and Operational Analysis of Compensation for Spare Part Replacement in Car Rental Services Perspective Wahbah Zuhaili - Sobri, Muhammad Arif; Pasaribu, Ilhamsyah (ASAS, 2024)
This study aims to analyze compensation due to the exchange of original spare parts by rental car renters from the perspective of Wahbah Zuhaili, with a case study on car rental company in Binjai City. The main problem faced by rental companies is financial and operational losses due to the actions of tenants who replace original spare parts with non-original ones. This study uses an empirical juridical approach with a case study method to explore how Islamic law, especially according to Wahbah Zuhaili's view, can be applied in this context. According to Wahbah Zuhaili, the tenant has full responsibility to maintain the rented goods and compensate for losses incurred due to negligence or intentional damage to the goods. In this case, the exchange of original spare parts with non-original ones by the lessee is a form of breach of contract and harms the car rental company. Islamic law stipulates that tenants are obliged to pay compensation equivalent to the value of the losses incurred. The results of the analysis show that the application of Islamic legal principles can provide justice for the aggrieved party. This study also found that the principle of compensation in Islamic law is in line with the positive law that applies in Indonesia. The study suggests that car rental companies strengthen clauses in lease agreements to protect their assets and ensure renters understand their responsibilitiesKeywords: Compensation; Sperpart Exchange; Wahbah Zuhaili's Thoughts;